Perspectives on the Integration of Psychology and Theology - Narramore, Bruce (Journal of psychology and theology, 1973)
As editor of the Journal of Psychology and Theology the author sketches the main purposes of this new publication. A statement of the goals of the editorial committee is followed by a brief evaluation of the present status of efforts to integrate biblical and psychological truth, a survey of some factors that have hindered the progress of integrative endeavors, and some suggestions for potentially fruitful areas of study and interaction.